Study on Dynamic Response of Rock Slope With Inverse Non-Persistent Joints Under Earthquake - Guo, Longxiao; Wu, Yihan; Ren, Kaihui; Zheng, Lu; Zhang, Hong (Frontiers in Earth Science, 2022)
Based on the two-dimensional discrete element software UDEC, this paper studied the dynamic response laws of rock slope with inverse non-persistent joints by the combination of different dip angles and spacing of join and length of rock bridge under earthquake. The results showed that the existence of the joint surface had a significant impact on the dynamic response of the slope. When the dip angle of inverse non-persistent joint increases or the joint spacing decreases, the PGA amplification factor of each monitoring point on the slope surface increases, and the influence range is mainly concentrated in the middle of the slope surface to the slope shoulder. Along the horizontal direction of the slope, the closer to the shoulder of the slope, the PGA amplification factor increases with the increase of joint dip angle and the decrease of rock bridge length and joint spacing; along the vertical direction, the PGA amplification coefficient curve increases firstly, then decreases, and then increases with the change of elevation, and the dynamic response of slope reacts the most violent where the joints are densely developed.